2008
DOI: 10.1152/jn.00949.2007
|View full text |Cite
|
Sign up to set email alerts
|

The Pool of Fast Releasing Vesicles Is Augmented by Myosin Light Chain Kinase Inhibition at the Calyx of Held Synapse

Abstract: Synaptic strength is determined by release probability and the size of the readily releasable pool of docked vesicles. Here we describe the effects of blocking myosin light chain kinase (MLCK), a cytoskeletal regulatory protein thought to be involved in myosin-mediated vesicle transport, on synaptic transmission at the mouse calyx of Held synapse. Application of three different MLCK inhibitors increased the amplitude of the early excitatory postsynaptic currents (EPSCs) in a stimulus train, without affecting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 80 publications
4
48
2
Order By: Relevance
“…Coaddition to the bath solution of a specific inhibitor of MLCK fully prevented/reverted all functional and ultrastructural changes induced by ROCK inhibition. These results are consistent with those reported at the calyx of Held synapse, in which MLCK was shown to control the size of the pool of fast releasing vesicles (Srinivasan et al, 2008). The finding that MLCK inhibition per se failed to modify both p-MLC levels and the amplitude of eEPSCs further suggests that basal activity of MLCK in our experimental preparation is low enough so that its effects on the actomyosin apparatus were relegated to the synaptic vesicle pool.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Coaddition to the bath solution of a specific inhibitor of MLCK fully prevented/reverted all functional and ultrastructural changes induced by ROCK inhibition. These results are consistent with those reported at the calyx of Held synapse, in which MLCK was shown to control the size of the pool of fast releasing vesicles (Srinivasan et al, 2008). The finding that MLCK inhibition per se failed to modify both p-MLC levels and the amplitude of eEPSCs further suggests that basal activity of MLCK in our experimental preparation is low enough so that its effects on the actomyosin apparatus were relegated to the synaptic vesicle pool.…”
supporting
confidence: 92%
“…It is thus possible that ROCK modulates neurotransmitter release and electrical activity of neuronal circuits through its cytoskeletaldependent regulation of presynaptic vesicle pools. This hypothesis gains support from the finding that MLCK controls the size of the pool of fast releasing vesicles at the calyx of Held (Srinivasan et al, 2008).…”
Section: Introductionmentioning
confidence: 80%
“…However, we did not observed any difference in late steady-state neurotransmission during 100 Hz stimulation in the presence of MLCK inhibitor or blebbistatin, suggesting that inhibition of MLCK has little effect on the vesicle recruitment during TS. Consistent with this view, Srinivasan et al (2008) have recently reported that ML-7 affects neither the steady-state EPSCs nor the rate of recovery from synaptic depression. Therefore, we imagine that the mechanisms underlying posttetanic increase in the RRP size might be different from that underlying replenishment of fast SV pool after depletion.…”
Section: Role Of Mlck In the Posttetanic Increase In The Rrp Sizementioning
confidence: 82%
“…5Bc). ML-7 increased the basal EPSC amplitude by 28.5 Ϯ 12.1 and 42.3 Ϯ 15.6% in the presence of Kyn or ␥-DGG, respectively, probably because of recruitment of the fast-releasing SV pool (Srinivasan et al, 2008). This can result in occlusion of posttetanic increase in the RRP size.…”
Section: Mlck Inhibitors Abolish Specifically the Posttetanic Increasmentioning
confidence: 97%
“…A possible experiment to determine whether the mechanisms responsible for the rundown are related to the need for energy for vesicular docking and recycling (i.e., they are ATP-dependent processes) could be one in which the rapid release of caged ATP within depressed terminals is induced as was similarly approached with release of Ca2+ from caged compounds [46]. It would be interesting to examine, within this preparation, the possibility of the myosin light chain kinase induced inhibition of vesicular movement as shown in the Calyx of held synapse [47]. Comparative studies with NMJs in Drosophila that show marked synaptic depression might prove to be fruitful [4,48].…”
Section: Table (1) Rrp and Docked Vesicle Analysismentioning
confidence: 99%